Pendampingan Guru Dalam Menerapkan Strategi Pengenalan Membaca Phonics Method - Ngura, Elisabeth; Fono, Yasinta Maria; Efrasia Odo, Maria (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The purpose of this community service activity is to explain how to introduce vocabulary reading strategies through the phonics method to teachers at Kober Peupado Malanuza and to explain the output products generated through the phonics strategy in this community service activity. The phonics method is one of the reading methods, where " teachers instruct students on how letter sounds are produced and blended and how to blend sounds together to form words. The phonics method is a reading technique that emphasizes the sounds (pronunciation) produced by the letters in a word. These sounds can differ from the letter names. Additionally, the advantage of this method is that it makes it easier for students to make automatic connections between words and sounds, allowing students to pronounce and read them independently." The outcome of this mentoring activity is that teachers are able to understand and apply basic literacy in accordance with the rules of good and correct Indonesian. One constraint of this activity is that teachers use old methods to pronounce letters, but this can be overcome with continuous practice